Expectancy-value appraisals and achievement emotions in an online learning environment: Within- and between-person relationships. (February 2022) - Berweger, Belinda; Born, Sebastian; Dietrich, Julia
Abstract: Motivation and emotion are of critical importance for students' academic learning and achievement. Drawing on Eccles and Wigfield's situated expectancy-value theory and Pekrun's control-value theory, we examined to what extent specific expectancy-value appraisals related to studentsʼ achievement emotions. We collected intensive state data of N  = 95 university students over one semester in an online learning environment. Students' appraisals were analyzed on different aggregation levels in a hierarchical design, which accounts for variability within learning situations and between students. Our results corroborated theoretical assumptions that expectancy-value appraisals are positively associated with positive emotions and negatively with negative emotions. However, we found that students experienced positive emotions in learning situations of high intrinsic and utility value, but not in situations of high attainment value. Examining appraisal combinations and discrete emotions, we found that particularly studentsʼ perceived costs moderated the relationship between expectancy and frustration and boredom on the situation level. Highlights: Pekrunʼs and Eccles et al.ʼs Expectancy-Value Models were combined. Between-person differences were disentangled from situational processes. We examined the moderating role of task values in the expectancy-emotion link. Studentsʼ positive values related in different ways to positive emotions. The cost value moderated the relationship between expectancy and negative emotions.